Susceptibility profile and associated factors of urinary tract infections among women with established preterm labor delivering at a tertiary teaching hospital in Eastern Uganda: a cross-sectional study - Abdirizak Ahmed Ifrah; Marie Pascaline Sabine Ishimwe; Carlos Antonio Batista Cedeño; Eilu Emmanuel; Theoneste Hakizimana (BMC Pregnancy and Childbirth)
Abstract Background Urinary tract infections have been recognized as a significant health issue since ancient times, but they are particularly concerning during pregnancy due to their potential to cause severe complications like preterm labor and low birth weight leading to significant neonatal morbidity and mortality. This study aimed to determine the prevalence, antibiotic susceptibility and factors associated with urinary tract infections among women with established preterm labor at Jinja Regional Referral Hospital. Methods This was a hospital-based cross-sectional study carried out from 1st January 2024 to 30th April 2024. Using a consecutive sampling method, 385 pregnant women were enrolled until the desired sample size was reached. Data was collected via pretested questionnaires, and antibiotic susceptibility patterns were determined via urine culture and sensitivity. Data was analysed using STATA Version 14.2. Bivariate and multivariate analyses were used to determine association between the dependent and independent variables, with P < 0.05 as the level of significance at 95% confidence interval. The results were presented in pie charts, bar graphs and tables. Results The prevalence of urinary tract infection was 114 (29.6%). The effectiveness of antibiotics against common Urinary tract Infection (UTI) pathogens varied significantly. E. coli was the most frequently isolated organism in UTIs, accounting for 42.98% of the cases followed by Enterococcus at 24.56%. Ceftriaxone was the most effective agent overall, with 81% of the pathogens showing susceptibility, followed by cefixime (78%) and co-amoxiclav (73%). Nitrofurantoin (64%) and cefuroxime (66%) had moderate effectiveness, whereas ampicillin (50%) was less effective. Azithromycin (34%) and erythromycin (28%) were the least effective. No formal education, being unemployed, monthly income less than 500,000 Ugandan Shillings, a history of urinary tract infection, Parity of one or more, a gestational age ≥ 26 weeks and diabetes (aOR = 8.00; 95% CI = [1.75–36.48]; P = 0.007), (aOR = 2.72; 95% CI = [1.38–5.23]; P = 0.003), (aOR = 2.55; 95% CI = [1.29–5.16]; P = 0.007), (aOR = 4.60; 95% CI = [2.64–8.25]; P < 0.001), (aOR = 1.90; 95% CI = [1.07–3.45]; P = 0.028), (aOR = 2.41; 95% CI = [1.17–4.92]; P = 0.017), (aOR = 3.11; 95% CI = [1.33–7.12]; P = 0.009), respectively, were significantly associated with urinary tract infection. Conclusions In this study, the prevalence of urinary tract infection was high compared with the worldwide prevalence. The majority of the isolates were susceptible to ceftriaxone, followed by co-amoxiclav, cefixime, nitrofurantoin, ampicillin, azithromycin and erythromycin. Primary or no formal education, monthly income ≤ 500,000Ugandan shillings, history of urinary tract infections, gestational age ≥ 26 weeks and diabetes were significantly associated with urinary tract infection.